Boron nitride ceramic and nickel-based superalloy connecting joint and preparation method thereof

By using a multi-layer structure design and solder reaction to generate TiN and TiB2, the problem of joining boron nitride ceramics with nickel-based superalloys is solved, achieving a high-strength connection suitable for thermal management of high-temperature thermal structural materials, and applicable to aerospace and nuclear energy fields.

CN121377808APending Publication Date: 2026-01-23CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511569665.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing technologies make it difficult to achieve effective and high-strength bonding between boron nitride ceramics and nickel-based superalloys, which limits the application of boron nitride ceramics in thermal management of high-temperature thermal structural materials.

Method used

The connector adopts a multi-layer structure design, including boron nitride ceramic, an intermediate layer and a nickel-based superalloy. The intermediate layer consists of a solder-boron nitride reaction layer, a solder reaction layer and a solder-nickel-based superalloy reaction layer. TiN and TiB2 are generated by the reaction of solder and boron nitride, which improves interface wetting and provides chemical bonding. Combined with the thermal expansion coefficient gradient of Ti layer and titanium alloy, thermal stress is reduced.

Benefits of technology

It achieves an effective and high-strength connection between boron nitride ceramics and nickel-based superalloys, with shear strength reaching 0.4-4 MPa, improving thermal stability and service life, and is suitable for aerospace and nuclear energy fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121377808A_ABST
    Figure CN121377808A_ABST
Patent Text Reader

Abstract

The invention relates to a boron nitride ceramic and nickel-based superalloy connecting joint and a preparation method thereof, belongs to the technical field of ceramic / metal composite structures, and solves the problem that a structure for effectively connecting boron nitride ceramic and nickel-based superalloy in a micro-level at high strength does not exist in the prior art. The connecting joint comprises boron nitride ceramic, a middle layer and a nickel-based high-temperature alloy which are sequentially connected, wherein the middle layer comprises a brazing filler metal-boron nitride reaction layer, a brazing filler metal reaction layer and a brazing filler metal-nickel-based high-temperature alloy reaction layer; the brazing filler metal-boron nitride reaction layer contains TiN; the brazing filler metal-boron nitride reaction layer in the connecting joint can effectively connect the boron nitride ceramic and the nickel-based high-temperature alloy; through the boron nitride-Ti layer reaction layer, the Ti layer and the brazing filler metal-Ti layer reaction layer, high-strength connection between the boron nitride ceramic and the nickel-based high-temperature alloy can be achieved; the connection joint can promote boron nitride ceramic to be effectively applied to thermal management of high-temperature thermal structure materials in the fields of aerospace, nuclear energy and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of ceramic / metal composite structure, in particular to a connecting joint of boron nitride ceramic and nickel-based superalloy and a preparation method thereof. BACKGROUND

[0002] The composite structure of ceramic and metal material can combine the advantages of ceramic and metal and make up for the shortcomings of each other, so as to obtain the comprehensive excellent performance that single material cannot achieve, such as excellent strong and tough combination performance, excellent wear resistance, high heat resistance and thermal shock resistance, synergy and optimization of functional characteristics, and strong designability.

[0003] Due to the difference in physical and chemical properties between ceramic and metal, it is difficult to effectively and high-strengthly combine the two. The high melting point and high brittleness of ceramic make it impossible to effectively connect the two by traditional melting welding and pressure welding. At present, although brazing uses lower melting filler metal to effectively connect part of ceramic (such as SiC and Si3N4) and metal through interfacial reaction, the inertness of boron nitride ceramic leads to almost no interfacial reaction with the existing filler metal, so it is difficult to effectively connect the two. Therefore, there is no connecting joint of boron nitride ceramic and nickel-based superalloy at present, which limits the application of boron nitride ceramic in thermal management of high-temperature thermal structure materials. SUMMARY

[0004] In view of the above analysis, the embodiments of the present application aim to provide a connecting joint of boron nitride ceramic and nickel-based superalloy and a preparation method thereof, to solve at least one of the problems that the existing technology does not effectively and high-strengthly connect boron nitride ceramic and nickel-based superalloy from the micro level.

[0005] In one aspect, the embodiments of the present application provide a connecting joint of boron nitride ceramic and nickel-based superalloy, which comprises boron nitride ceramic, an intermediate layer and nickel-based superalloy connected in sequence, wherein, from the direction of the boron nitride ceramic to the nickel-based superalloy, the intermediate layer comprises a filler metal-boron nitride reaction layer, a filler metal reaction layer and a filler metal-nickel-based superalloy reaction layer; the filler metal-boron nitride reaction layer contains TiN.

[0006] Further, the filler metal-boron nitride reaction layer comprises a boron nitride-Ti layer reaction layer, a Ti layer and a filler metal-Ti layer reaction layer.

[0007] Further, the boron nitride ceramic is hexagonal boron nitride ceramic.

[0008] Further, the boron nitride ceramic is a sheet or a block.

[0009] Further, the boron nitride-Ti layer reaction layer contains TiN.

[0010] Further, the thickness of the boron nitride-Ti layer reaction layer is 0.1-0.5 μm.

[0011] Further, the thickness of the titanium layer is 1-4 μm.

[0012] Further, the thickness of the solder-Ti layer reaction layer is 0.1-0.5 μm.

[0013] Further, the raw material of the solder reaction layer contains nickel-based amorphous powder and titanium hydride powder, and the mass ratio of the two is 9:1-7:3.

[0014] Further, the thickness of the solder reaction layer is 20-200 μm.

[0015] Further, the solder-nickel-based high-temperature alloy reaction layer is a metal cladding layer.

[0016] Further, the thickness of the metal cladding layer is 5-25 μm.

[0017] Further, the shear strength of the connecting joint is 0.4-4 MPa.

[0018] In another aspect, the embodiment of the present application provides a method for preparing the connecting joint of the boron nitride ceramic and the nickel-based high-temperature alloy, and the method comprises:

[0019] (1) preparing a nickel-based composite solder;

[0020] (2) placing the nickel-based composite solder between the surfaces to be welded of the boron nitride ceramic and the nickel-based high-temperature alloy, and pressing with a mold;

[0021] (3) heat treatment, to obtain the connecting joint.

[0022] Further, before step (2) is performed, it further comprises depositing a titanium film on the surface to be welded of the boron nitride ceramic.

[0023] Compared with the prior art, the present application can at least achieve one of the following beneficial effects:

[0024] 1. Compared with the prior art, the present application first proposes the connecting joint of the boron nitride ceramic and the nickel-based high-temperature alloy, which contains a solder-boron nitride reaction layer generated by the reaction of the solder containing nickel and boron nitride, so that the boron nitride ceramic with strong chemical inertness and the nickel-based high-temperature alloy are effectively combined from the micro level, wherein the TiN and TiB2 contained in the solder-boron nitride reaction layer can improve the interface wetting of the BN ceramic and titanium or titanium alloy, provide chemical bonding between the BN ceramic and the solder reaction layer, play the role of strengthening phase, and enhance the interface bonding.

[0025] 2、The present application adjusts the composition structure of the brazing filler-nitride boron reaction layer, on one hand, the TiN and TiB2 contained in the nitride boron-Ti layer reaction layer can improve the bonding strength between the nitride boron ceramic and the Ti layer, and meanwhile, the effective and high-strength connection between the nitride boron ceramic and the brazing filler reaction layer is realized through the metal cladding layer between the brazing filler and the Ti layer; on the other hand, the multilayer structure of the brazing filler-nitride boron reaction layer has different thermal expansion coefficients, so that the connecting joint between the ceramic and the brazing filler has gradient thermal stress behavior, the thermal stress between the two is reduced, the thermal stability in the actual use process of the connecting joint is improved, and the service life is prolonged.

[0026] 3、The present application adjusts the thickness of each layer of the intermediate layer constituting the connecting joint, which can realize effective and high-strength connection between the nitride boron ceramic and the nickel-based high-temperature alloy, avoid interface embrittlement caused by the too thick intermediate layer, and reduce the mechanical strength of the connecting member.

[0027] In the present application, the above technical solutions can be combined with each other to realize more preferred combination solutions. Other features and advantages of the present application will be described in the subsequent specification, and some advantages will become apparent from the specification, or will be understood by implementing the present application. The purposes and other advantages of the present application can be realized and obtained from the contents specifically pointed out in the specification and the drawings. BRIEF DESCRIPTION OF DRAWINGS

[0028] The accompanying drawings are included to provide a further understanding of the application and are incorporated in and constitute a part of this specification, illustrate embodiments of the application and together with the description serve to explain the principles of the application. In the drawings:

[0029] Figure 1 It is a structural schematic diagram of the connecting joint of the present application;

[0030] Figure 2 It is a SEM picture of the connecting joint of the present application;

[0031] Figure 3 It is a physical picture of the connecting joint of the present application;

[0032] Figure 4 It is a process schematic diagram for preparing the connecting joint of the present application;

[0033] REFERENCE NUMERALS:

[0034] 1-Ni-based high-temperature alloy; 2-nickel-based high-temperature alloy-brazing filler reaction layer; 3-brazing filler layer; 4-brazing filler-Ti layer reaction layer; 5-Ti layer; 6-Ti layer-nitride boron reaction layer; 7-BN ceramic. DETAILED DESCRIPTION

[0035] The preferred embodiments of the present application will be described in detail below with reference to the drawings, wherein the drawings constitute a part of the present application and serve to explain the principles of the present application together with the embodiments of the present application, but are not intended to limit the scope of the present application.

[0036] The boron nitride ceramic has extremely high thermal stability and excellent thermal conductivity, is expected to be applied to the thermal management of high-temperature thermal structural materials, and is a material with development potential in the fields of aerospace and nuclear energy; the application of the boron nitride ceramic often requires the connection of the boron nitride ceramic and metal, and the inertness of the boron nitride ceramic makes it difficult to react with the existing low-temperature brazing filler metal, and the boron nitride ceramic and the metal high-temperature thermal structural material cannot be effectively connected by brazing, in addition, the significant difference in the thermal expansion coefficient between the boron nitride ceramic and the metal further hinders the connection between the two.

[0037] Therefore, the present application discloses a connection joint of boron nitride ceramic and nickel-based high-temperature alloy, a structural schematic diagram of which is shown as Figure 1 The connection joint comprises boron nitride ceramic, intermediate layer and nickel-based high-temperature alloy connected in sequence, wherein, from the boron nitride ceramic to the nickel-based high-temperature alloy, the intermediate layer comprises brazing filler metal-boron nitride reaction layer, brazing filler metal reaction layer and brazing filler metal-nickel-based high-temperature alloy reaction layer; the brazing filler metal-boron nitride reaction layer contains TiN.

[0038] Compared with the prior art, the present application first proposes a connection joint of boron nitride ceramic and nickel-based high-temperature alloy, which contains a brazing filler metal-boron nitride reaction layer generated by the reaction of the brazing filler metal containing nickel and boron nitride, so that the boron nitride ceramic with strong chemical inertness and the nickel-based high-temperature alloy are effectively combined at the micro level, wherein, the TiN and TiB2 contained in the brazing filler metal-boron nitride reaction layer can improve the interface wetting of the BN ceramic and titanium or titanium alloy, provide chemical bonding between the BN ceramic and the brazing filler metal reaction layer, play the role of strengthening phase, and enhance the interface bonding.

[0039] It should be noted that, considering the thermal stability and thermal conductivity of boron nitride, as well as the processing feasibility and economic cost, the present application needs to limit the type of boron nitride.

[0040] Specifically, the boron nitride ceramic in the present application is hexagonal boron nitride ceramic.

[0041] It should be noted that, in order to adapt to the application of boron nitride ceramic in the thermal management of high-temperature thermal structural materials, the present application needs to limit the structure and shape of the boron nitride ceramic.

[0042] Specifically, the boron nitride ceramic in the present application is a sheet or a block.

[0043] It should be noted that, in order to enhance the effective connection between the boron nitride ceramic and the brazing filler metal, the brazing filler metal-boron nitride reaction layer between the two is designed as a multi-layer structure.

[0044] Specifically, the brazing filler metal-boron nitride reaction layer comprises a boron nitride-Ti layer reaction layer, a Ti layer, and a brazing filler metal-Ti layer reaction layer.

[0045] It should be noted that, in order to improve the effective connection between the boron nitride ceramic and the Ti layer, while avoiding the interface embrittlement, the present application needs to adjust the composition and thickness of the boron nitride-Ti layer reaction layer obtained by the reaction of the two.

[0046] Specifically, the boron nitride-Ti layer reaction layer contains TiN and TiB2, wherein, due to the diffusion of nitrogen being much faster than that of boron during the preparation process, nitrogen is more likely to react with titanium to form TiN from the side of the boron nitride ceramic, while boron lags behind and forms TiB2 on the side close to BN.

[0047] It should be noted that TiN has a face-centered cubic structure, high hardness, high chemical stability, excellent metal conductivity, and good lattice matching with Ti, effectively blocking the further diffusion of B atoms to the Ti matrix and inhibiting the excessive growth of the reaction layer; its thermal expansion coefficient is between Ti and TiB2 / BN, which helps to relieve thermal mismatch stress; compared with TiB2, TiN has a certain toughness and can prevent crack propagation.

[0048] It should be noted that TiB2 (titanium diboride) has a hexagonal structure, extremely high hardness, high melting point, high wear resistance, excellent metal conductivity and thermal conductivity, and is the main contributor to the interface strength; it has similarity with BN crystal structure (both are hexagonal), has crystallographic continuity with BN, and can form strong chemical bonding with BN, which is the "anchor point" connected to the BN ceramic and can effectively transfer the load from the relatively soft titanium matrix to the hard BN ceramic.

[0049] Specifically, the thickness of the boron nitride-Ti layer reaction layer is 0.1-0.5 μm, if the thickness is too large, it will cause the reaction layer to separate from the boron nitride base material; if the thickness is too small, it will not form a good stable connection, and can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, or 0.5 μm.

[0050] It should be noted that, in order to improve the effective connection between the boron nitride ceramic and the brazing filler metal, while relieving the concentration of interface thermal stress and preventing the embrittlement of the interface, the present application needs to limit the thickness of the titanium layer.

[0051] More specifically, the thickness of the titanium layer is 1-4 μm. If the thickness of the titanium layer is too large, it will cause the titanium layer itself to delaminate and break; if the thickness of the titanium layer is too small, it will lose the effect of relieving thermal stress, and can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, or 4 μm.

[0052] It should be noted that, in order to avoid interface embrittlement while ensuring the connection strength between the Ti layer and the filler layer, the present application needs to limit the thickness of the filler-Ti layer reaction layer.

[0053] Specifically, the thickness of the filler-Ti layer reaction layer is 0.1-0.5 μm. If the thickness of the reaction layer is too large, it will cause interface brittleness and lower joint strength; if the thickness of the reaction layer is too small, it will cause ineffective connection. It can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm.

[0054] It should be noted that, in order to obtain the best performance of the welded joint, the present application needs to limit the thickness of the filler reaction layer.

[0055] Specifically, the thickness of the filler reaction layer is 20-200 μm. If the thickness of the filler reaction layer is too large, it will cause insufficient reaction of the filler, too many interface compounds, and a decrease in joint strength; if the thickness of the filler reaction layer is too small, it will cause ineffective connection. It can be 20 μm, 40 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, 200 μm.

[0056] It should be noted that, in order to better achieve connection, the present application needs to limit the thickness of the metal cladding layer as the filler-nickel-based high-temperature alloy reaction layer.

[0057] Specifically, the thickness of the metal cladding layer is 5-25 μm. If the filler-nickel-based high-temperature alloy reaction layer is too large, it will cause erosion of the base material and affect the performance of the base material; if the thickness of the filler-nickel-based high-temperature alloy reaction layer is too small, it will cause low bonding strength, which can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm.

[0058] It should be noted that the connection joint of boron nitride ceramic and nickel-based high-temperature alloy provided by the present application not only realizes effective connection between boron nitride ceramic and nickel-based high-temperature alloy, but also realizes high-strength connection of the connection joint through structure optimization.

[0059] Specifically, the shear strength of the connection joint is 0.4-4 MPa.

[0060] On the other hand, the present application also provides a method for preparing the connection joint of boron nitride ceramic and nickel-based high-temperature alloy, and the specific process flow is as shown in Figure 4 The method comprises:

[0061] (1) preparing a nickel-based composite filler;

[0062] (2) placing the nickel-based composite filler between the boron nitride ceramic and the nickel-based high-temperature alloy to be welded, and pressing the mold;

[0063] (3) heat treatment, to obtain the connecting joint.

[0064] It should be noted that, in order to improve the adhesion strength of the titanium film on the surface of the BN ceramic and the wettability of the filler metal on the surface of the Ni-based superalloy, it is necessary to remove contaminants on the welding surface of the two, which are one or more of oxide film, adsorbed water film, organic oil stain and metal debris.

[0065] Specifically, before step (1) is performed, the surface to be welded of the boron nitride ceramic and the surface to be welded of the nickel-based superalloy are polished and cleaned respectively.

[0066] According to some preferred embodiments of the present application, the surface to be welded of the boron nitride ceramic and the surface to be welded of the nickel-based superalloy are polished with No. 1000 sandpaper and then cleaned with acetone for 10 minutes.

[0067] It should be noted that, in order to enable the boron nitride ceramic with strong chemical inertness not only to perform interfacial reaction with the filler metal and achieve effective connection with the nickel-based superalloy, but also to enhance the effective connection, the present application needs to perform modification treatment on the surface to be tested of the boron nitride ceramic.

[0068] Specifically, before step (2) is performed, it further includes depositing a titanium film on the surface to be welded of the boron nitride ceramic.

[0069] It should be noted that, in the subsequent vacuum heat treatment of connecting the BN ceramic and the Ni-based superalloy by using the nickel-based composite filler metal, on the one hand, the side of the titanium layer in contact with the BN ceramic reacts with the BN to form a TiN thin layer, the TiN has good wetting and pinning effect on the boron nitride, which can improve the bonding strength between the titanium layer and the BN ceramic; on the other hand, the other side of the titanium layer away from the BN ceramic reacts with the nickel-based composite filler metal to form intermetallic compounds such as TiNi, at the same time, the nickel-based composite filler metal is high-temperature solid-solved with the Ni-based superalloy; wherein, the titanium nitride layer generated by alloy reaction, the titanium layer and the intermetallic compound layer provide gradient materials with different thermal expansion coefficients, greatly reducing the interfacial thermal stress generated when connecting the ceramic and the metal during heat treatment, thereby achieving effective connection of the two.

[0070] It should be noted that, in order to improve the adhesion and density of the titanium film on the surface of the ceramic, and accurately control the thickness of the film layer to the micro-nanometer level, the present application adopts a magnetron sputtering method to plate a titanium film on the surface to be welded of the cleaned boron nitride ceramic.

[0071] More specifically, in step (2), the present application adopts a magnetron sputtering method to plate a titanium film on the surface to be welded of the cleaned boron nitride ceramic, and the specific conditions are: vacuum degree is 5×10 -5 Pa-7×10 -5The argon pressure is 0.5 Pa to 2 Pa, the target distance is 100 mm to 190 mm, the direct current power is 180 W to 220 W, and the time is 2 h to 8 h.

[0072] It should be noted that, in order to prevent the titanium film from being oxidized during preparation, the base vacuum degree of the magnetron sputtering needs to be limited; appropriate argon pressure, target distance and power can cooperatively ensure the adhesion, uniformity and density of the titanium film; and the length of the sputtering time determines the thickness of the titanium film.

[0073] According to some preferred embodiments of the present application, the vacuum degree of the magnetron sputtering can be 5*10 -5 Pa to 7*10 -5 Pa, such as 5*10 -5 Pa, 5.5*10 -5 Pa, 6*10 -5 Pa, 6.5*10 -5 Pa, 7*10 -5 Pa.

[0074] According to some preferred embodiments of the present application, the argon pressure of the magnetron sputtering can be any value in the range of 0.5 Pa to 2 Pa, such as 0.5 Pa, 0.8 Pa, 1 Pa, 1.2 Pa, 1.5 Pa, 1.7 Pa, 2 Pa; the target distance of the magnetron sputtering can be any value in the range of 100 mm to 190 mm, such as 100 mm, 110 mm, 120 mm, 130 mm, 140 mm, 150 mm, 160 mm, 170 mm, 180 mm, 190 mm; and the direct current power of the magnetron sputtering can be any value in the range of 180 W to 220 W, such as 180 W, 190 W, 200 W, 210 W, 220 W.

[0075] It should be noted that, in order to facilitate the interface reaction between the titanium layer and the ceramic surface and the interface reaction between the titanium layer and the composite filler during subsequent heat treatment, and to realize effective (no cracks at the interface) and high-strength connection of the BN ceramic and the Ni-based high-temperature metal, the thickness of the titanium film plated on the surface of the BN ceramic needs to be limited.

[0076] Specifically, in step (2), the thickness of the titanium film is 1-4 μm.

[0077] According to some preferred embodiments of the present application, the thickness of the titanium film can be any value in the range of 1-4 μm, such as 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, or 4 μm. If the titanium film is too thin, it will be completely reacted with the BN ceramic and the filler metal during the subsequent brazing heat treatment, and cannot form an intermediate layer with sufficient gradient structure between the ceramic to be welded and the nickel-based superalloy, resulting in joint failure due to internal stress; if the titanium film is too thick, the joint will also fail due to the poor strength of the titanium film itself. Within the above thickness range defined in the present application, a higher joint strength can be obtained.

[0078] It should be noted that, in order to prevent the excessive reaction of the nickel-based amorphous powder filler metal with the titanium film during the brazing heat treatment, and to affect the interfacial reaction and bonding strength between the titanium film and the boron nitride, the present application needs to design the composition of the filler metal.

[0079] Specifically, in step (3), the nickel-based composite filler metal comprises nickel-based amorphous powder and titanium hydride powder, and the mass ratio of the nickel-based amorphous powder to the titanium hydride powder is 7:3-9:1.

[0080] It should be noted that, compared with pure Ti, the titanium hydride in the composite filler metal of the present application has higher chemical stability, is not easy to be oxidized during the ball milling mixing process with the Ni-based amorphous powder and the subsequent heat treatment brazing process, and can generate titanium by dehydrogenation when the temperature is greater than 400℃, thereby efficiently participating in the interfacial reaction of brazing and fully playing its regulating role, which is more conducive to the effective and high-strength connection between the BN ceramic and the nickel-based superalloy.

[0081] According to some preferred embodiments of the present application, the mass ratio of the nickel-based amorphous powder to the titanium hydride powder of the titanium film can be any value in the range of 7:3-9:1, such as 7:3, 7.5:2.5, 8:2, 8.5:1.5, or 9:1. Too little titanium hydride content will cause the self-reaction of the nickel-based amorphous filler metal with the titanium hydride instead of the reaction with the titanium layer, resulting in reduced bonding strength between the titanium layer and the filler metal layer, and too high titanium hydride content will cause the melting point of the filler metal to be too high and the joint to have too many brittle phase compounds, thereby reducing the joint strength. Within the above filler metal content range of the present application, a joint with better welding quality can be obtained.

[0082] It should be noted that, in terms of weight percentage, the nickel-based amorphous powder comprises B 2.75%-3.5%, Si 4%-5%, Cr 6.0%-8.0%, Fe 2.5%-3.5%, carbon ≤0.06%, and the balance of Ni.

[0083] It should be noted that, in order to fully and uniformly mix the components of the composite filler metal, the present application needs to limit the mixing method of the nickel-based amorphous powder and the titanium hydride powder.

[0084] Specifically, in step (3), the nickel-based composite filler is obtained by mixing raw materials by vacuum ball milling, and the specific method comprises the following steps: according to the mass ratio, the nickel-based amorphous filler powder and titanium hydride powder are placed in a vacuum ball mill tank, the ball-to-material ratio is 10:1-20:1, vacuum is drawn, nitrogen protection is injected, and ball milling is carried out at a speed of 80-120 rpm under a nitrogen atmosphere of 0.1-0.3 MPa for 10-30 min.

[0085] According to some preferred embodiments of the present application, the ball-to-material ratio can be any value in the range of 10:1-20:1, such as 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, or 20:1; too low a ball-to-material ratio can easily lead to uneven mixing; and too high a ball-to-material ratio can lead to excessive grinding energy, smaller powder size, and poor mixing.

[0086] It should be noted that, in order to prevent oxidation of the filler material during ball milling, nitrogen protection is injected into the vacuum ball mill tank, and the raw materials are mixed under a nitrogen atmosphere of 0.1-0.3 MPa.

[0087] According to some preferred embodiments of the present application, the ball milling nitrogen pressure can be any value in the range of 0.1-0.3 MPa, such as 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, or 0.3 MPa; if the pressure is too small, the raw materials can be easily oxidized during ball milling; and if the pressure is too large, the powder can be ejected during the opening of the tank due to pressure relief.

[0088] According to some preferred embodiments of the present application, the ball milling speed can be any value in the range of 80-120 rpm, such as 80 rpm, 85 rpm, 90 rpm, 95 rpm, 100 rpm, 105 rpm, 110 rpm, 115 rpm, or 120 rpm; if the speed is too high, the raw materials can be easily layered and mixed unevenly; and if the speed is too low, the mixing efficiency is low and a long ball milling time is required.

[0089] According to some preferred embodiments of the present application, the ball milling time can be any value in the range of 10-30 min, such as 10 min, 15 min, 20 min, 25 min, or 30 min; too short a time can lead to uneven mixing, and too long a time can easily cause the raw materials to be layered and mixed unevenly.

[0090] It should be noted that, in order to improve the efficiency of subsequent vacuum brazing, the present application needs to limit the size of the nickel-based amorphous powder and the titanium hydride powder that make up the composite filler.

[0091] Specifically, in step (3), the particle size of the nickel-based amorphous powder constituting the composite filler metal is 200-600 mesh, and the particle size of the titanium hydride powder is 600-800 mesh.

[0092] It should be noted that, in order to improve the wettability of the filler metal powder on the surface to be welded, and promote the interfacial bonding between the filler metal and the titanium layer and the nickel-based superalloy, the composite filler metal needs to be formulated into a solder paste before use.

[0093] Specifically, in step (4), the nickel-based composite filler metal is first formulated into a solder paste, and then the solder paste is placed between the boron nitride ceramic and the surface to be welded of the nickel-based superalloy.

[0094] Specifically, the paste carrier of the solder paste is rosin, acrylic resin, etc., and at least one of the organic solvents such as acetone and isopropyl alcohol is used.

[0095] It should be noted that, in order to improve the wettability of the composite filler metal on the surface to be welded, the solder paste can be formed and stably exist between the surfaces to be welded, the present application needs to limit the ratio between the nickel-based composite filler metal, the paste carrier and the solvent.

[0096] Specifically, the mass ratio of the nickel-based composite filler metal, the paste carrier and the solvent is 1:(1-3):(5-8).

[0097] It should be noted that, in order to ensure the strength of the brazing connection and avoid excessive brittle phase content in the intermediate layer, which affects the mechanical strength of the connection joint, the present application needs to control the amount of the solder paste.

[0098] Specifically, in step (4), the thickness of the solder paste placed between the boron nitride ceramic and the surface to be welded of the nickel-based superalloy is 50-200 μm; if the thickness of the solder paste is too thin, it will easily affect the interfacial bonding strength between the filler metal and the titanium layer and the nickel-based superalloy, and if the thickness is too thick, the filler metal will form an erosion effect on the base material, which is contrary to the original intention of brazing connection.

[0099] According to some preferred embodiments of the present application, the thickness of the solder paste placed between the boron nitride ceramic and the surface to be welded of the nickel-based superalloy can be any value within the range of 50-200 mm, such as 50 mm, 80 mm, 100 mm, 130 mm, 150 mm, 170 mm, 200 mm.

[0100] It should be noted that, in order to fix the relative position between the layers to be welded and ensure the brazing interfacial bonding quality, the present application needs to use a mold to press the boron nitride ceramic and the nickel-based superalloy with the composite filler metal placed between the surfaces to be welded, and limit the pressing pressure.

[0101] Specifically, in step (4), the graphite mold is used to press the to-be-welded ceramic and alloy, wherein the pressure of the mold pressing is 0.2-1 MPa. If the pressure is too large, the solder paste is easily squeezed out from the surfaces to be welded, and if the pressure is too small, the gas generated in the heat treatment process, including the gas generated by the thermal decomposition of the paste carrier and the hydrogen generated by the heating of titanium hydride, will cause bubbles to remain in the intermediate layer connecting the BN ceramic and the Ni-based superalloy, affecting the interface bonding strength of the joint.

[0102] According to some preferred embodiments of the present application, the pressure of the mold pressing can be any value in the range of 0.2-1 MPa, such as 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, or 1 MPa.

[0103] It should be noted that, in order to improve the interface bonding strength between the titanium layer and the boron nitride, and the reaction between the titanium layer and the solder, and to ensure that the physicochemical properties of the nickel-based superalloy are not affected by high temperature, and to maximize the intrinsic properties of the alloy, the present application needs to limit the brazing heat treatment process steps and process parameters.

[0104] Specifically, in step (5), the heat treatment method specifically includes: 3×10 -3 Pa~5×10 -3 Pa under vacuum, heated to 1000-1100℃, maintained for 5-25 min, and cooled; the vacuum environment of the heat treatment can avoid the oxidation of metal Ti to TiO2, affecting the reaction of the solder; the temperature and time of the heat treatment not only promote the solid-solid reaction between the titanium layer and the boron nitride to generate a TiN thin layer with higher bonding strength with the substrate, but also avoid the influence of high temperature on the physicochemical properties of the nickel-based superalloy.

[0105] According to some preferred embodiments of the present application, the vacuum degree of the heat treatment can be any value in the range of 3×10 -3 Pa~5×10 -3 Pa, such as 3×10 -3 Pa, 3.5×10 -3 Pa, 4×10 -3 Pa, 4.5×10 -3 Pa, or 5×10 -3 Pa.

[0106] According to some preferred embodiments of the present application, the temperature of the heat treatment is any value in the range of 1000-1100℃, such as 1000℃, 1020℃, 1050℃, 1080℃, or 1100℃.

[0107] In some preferred embodiments of the present application, the heat treatment time is any value in the range of 5 min to 25 min, such as 5 min, 7 min, 10 min, 12 min, 15 min, 18 min, 20 min, 23 min or 25 min.

[0108] It should be noted that, in order to facilitate the discharge of gas during the heating process of the heat treatment and improve the interface connection quality, the present application needs to limit the rate of the heating process.

[0109] Specifically, in step (5), the heating rate during the heat treatment is 8-12℃ / min. If the heating rate is too low, the heat treatment efficiency will be affected. If the heating rate is too high, the gas generated by the thermal decomposition (300-400℃) of the paste carrier and the hydrogen generated by the decomposition of titanium hydride will not be discharged in time, resulting in the existence of bubbles in the intermediate layer formed by the interface reaction between the filler metal and the titanium layer and the alloy surface, affecting the strength. In addition, a suitable heating rate can also make the titanium hydride in the composite filler metal completely volatilize hydrogen before the nickel-based amorphous filler metal is melted and brazed, so as to obtain pure Ti which really plays a role in brazing and timely and effectively prevent the excessive reaction between the nickel-based amorphous alloy and the Ti layer.

[0110] It should be noted that, in order to avoid excessive concentration of thermal stress due to the difference in thermal expansion coefficient between different component material layers during the cooling process of the heat treatment, causing cracks in the interface and leading to joint failure, the present application needs to limit the cooling method.

[0111] Specifically, in step (5), the cooling process of the heat treatment specifically includes: first reducing to 400-500℃ at a speed of 2-6℃ / min, and then furnace cooling to room temperature. Since the heat treatment temperature is too high, during the cooling and solidification process in the high temperature section (500-1100℃), the connection joint needs to be controlled to be cooled slowly by continuing to heat, so as to avoid thermal stress cracking at the brazing filler metal reaction interface. When the temperature reaches the low temperature section, the connection joint can be slowly cooled with the furnace.

[0112] The connection joint based on boron nitride ceramic and nickel-based high-temperature alloy prepared by the method of the present application not only realizes effective (no cracks in the interface bonding intermediate layer) and high bonding strength (the shear strength at room temperature is as high as 3.48MPa) connection between BN ceramic and nickel-based high-temperature alloy, but also maximizes the intrinsic properties of the Ni-based high-temperature alloy, so that the BN ceramic effectively connected therewith can truly play the role of thermal management high-temperature structural material, which is conducive to the popularization and application of BN ceramic in the fields of aerospace, nuclear energy and the like.

[0113] The present application will be further explained and described by the following examples and comparative examples.

[0114] Example 1

[0115] A connection joint between boron nitride ceramic and nickel-based superalloy, specifically comprising:

[0116] (1) The surfaces to be welded of GH4169 nickel-based high-temperature alloy and h-BN ceramic were polished with 1000 grit sandpaper and then ultrasonically cleaned with acetone for 10 min.

[0117] (2) The cleaned h-BN workpiece to be welded is placed into a magnetron sputtering equipment for magnetron sputtering titanium film deposition. The conditions include: a base vacuum of 5×10⁻⁶. -5 Pa, argon pressure 1 Pa, DC power supply power 200 W, coating time 6 h, a 3 μm thick titanium film was obtained on the h-BN ceramic surface.

[0118] (3) Nickel-based amorphous brazing filler powder (200 mesh) and titanium hydride powder (400 mesh) with a mass ratio of 9:1 were placed in a vacuum ball mill jar, vacuum was drawn, and nitrogen gas of 0.2 MPa was injected for protection. The ball-to-filler ratio was 15:1. The horizontal ball mill was rotated at 120 r / min and ground for 10 min to obtain a composite brazing filler. The composite brazing filler was then mixed with a solvent and a paste carrier to obtain a composite brazing filler paste. The mass ratio of the composite brazing filler to the solvent and paste carrier was 1:3:5.

[0119] (4) Place the composite solder paste obtained in step (3) between GH4169 and the coated hexagonal boron nitride ceramic to be soldered, with a thickness of 100mm, and press it with a graphite mold with a pressure of about 0.4MPa.

[0120] (5) Place it in a vacuum furnace and wait for the vacuum degree of the vacuum furnace to reach 4×10 -3 At Pa, the heating process involves raising the temperature to 1050℃ at a rate of 10℃ / min and holding it for 15min; then lowering the temperature to 400℃ at a rate of 5℃ / min, shutting off the heating, and allowing the furnace to cool to room temperature, thus obtaining the connection joint between h-BN ceramic and GH4169 nickel-based superalloy. The actual connection joint is shown in the image. Figure 3 As shown, the SEM image of connector 1 is as follows: Figure 2 As shown, from Figure 2 It can be seen that nickel-based superalloys and BN ceramics can achieve a tight bond at the microscopic level; the test results show that the shear strength of the joint at room temperature reaches 3.48 MPa.

[0121] Example 2

[0122] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 1. The difference was that in step (2), the coating time was 4 hours, and a 2 μm thick titanium film was obtained on the surface of the h-BN ceramic, and finally the connection joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained. The shear strength of the connection joint at room temperature reached 3.24 MPa.

[0123] Example 3

[0124] A connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared by the same method as in Example 1, except that in step (2), the plating time was 2 h, a 1-μm-thick titanium film was obtained on the surface of the h-BN ceramic, and finally a connecting joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained; the shear strength of the connecting joint at room temperature reached 2.99 MPa after testing.

[0125] Example 4

[0126] A connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared by the same method as in Example 1, except that in step (3), the mass ratio of nickel-based amorphous filler powder (200 mesh) to titanium hydride powder (400 mesh) was 8:2, and finally a connecting joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained; the shear strength of the connecting joint at room temperature reached 1.50 MPa after testing.

[0127] Example 5

[0128] A connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared by the same method as in Example 4, except that in step (2), the plating time was 4 h, a 2-μm-thick titanium film was obtained on the surface of the h-BN ceramic, and finally a connecting joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained; the shear strength of the connecting joint at room temperature reached 3.39 MPa after testing.

[0129] Example 6

[0130] A connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared by the same method as in Example 4, except that in step (2), the plating time was 2 h, a 1-μm-thick titanium film was obtained on the surface of the h-BN ceramic, and finally a connecting joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained; the shear strength of the connecting joint at room temperature reached 1.85 MPa after testing.

[0131] Example 7

[0132] A connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared by the same method as in Example 3, except that in step (3), the mass ratio of nickel-based amorphous filler powder (200 mesh) to titanium hydride powder (400 mesh) was 7:3, and finally a connecting joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained; the shear strength of the connecting joint at room temperature reached 1.24 MPa after testing.

[0133] Example 8

[0134] A connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared by the same method as in Example 1, except that in step (4), the thickness of the solder paste placed between the GH4169 and the plated hexagonal boron nitride ceramic was 150 mm, and finally a connecting joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained; the shear strength of the connecting joint at room temperature was 3.32 MPa after testing.

[0135] Example 9

[0136] A connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared by the same method as in Example 1, except that step (2) was not included, i.e., no titanium layer was prepared on the surface of the BN ceramic in Comparative Example 1, and finally a connecting joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained; the shear strength of the connecting joint at room temperature was 0.4 MPa after testing.

[0137] Example 10

[0138] A connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared by the same method as in Example 1, except that in step (2), the plating time was 1 h, and a 0.5 μm thick titanium film was obtained on the surface of the h-BN ceramic, and finally a connecting joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained; the connecting joint obtained by this method did not have a titanium layer, and the shear strength of the connecting joint at room temperature was 0.52 MPa.

[0139] Example 11

[0140] A connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared by the same method as in Example 1, except that in step (5), heating was carried out to 1000°C, and finally a connecting joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained; the shear strength of the connecting joint at room temperature was 2.95 MPa after testing.

[0141] Example 12

[0142] A connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared by the same method as in Example 1, except that in step (5), heating was carried out to 1100°C, and finally a connecting joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained; the shear strength of the connecting joint at room temperature was 3.26 MPa after testing.

[0143] Example 13

[0144] The same method as example 1 was used to prepare the connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy, except that in step (5), the holding time was 25 min, and finally the connecting joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained; the shear strength of the connecting joint at room temperature was 3.15 MPa.

[0145] Comparative example 1

[0146] The same method as example 1 was used to prepare the connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy, except that in step (2), the plating time was 8 h, and a 4 μm thick titanium film was obtained on the surface of the h-BN ceramic, and the connecting joint could not be obtained by the method of comparative example 1, because the titanium film was too thick, which led to the cracking of the titanium layer during heat treatment.

[0147] Comparative example 2

[0148] The same method as example 1 was used to prepare the connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy, except that in step (4), the thickness of the solder paste placed between the GH4169 and the soldered surface of the plated hexagonal boron nitride ceramic was 300 mm, and the obtained connecting joint did not form an effective connection, and the macroscopic fracture position was located in the middle of the solder.

[0149] Comparative example 3

[0150] The same method as example 1 was used to prepare the connecting joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy, except that in step (5), the heating temperature was 1150℃, and finally the connecting joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained; the GH4169 nickel-based superalloy in the connecting joint 16 showed obvious grain coarsening and softening.

[0151] The structure, size parameters and connecting performance of the connecting joints prepared by the above examples and comparative examples are shown in Table 1:

[0152] Table 1 Structure, size parameters and performance of the connecting joints of examples and comparative examples

[0153]

[0154]

[0155] The above is only the preferred specific embodiment of the present application, but the protection scope of the present application is not limited to this, any change or replacement easily thought by those skilled in the art within the technical range disclosed by the present application should be covered in the protection scope of the present application.

Claims

1. A connecting joint between boron nitride ceramic and nickel-based superalloy, characterized in that, The connector comprises a boron nitride ceramic, an intermediate layer, and a nickel-based superalloy connected in sequence. The intermediate layer, from the boron nitride ceramic to the nickel-based superalloy, comprises a solder-boron nitride reaction layer, a solder reaction layer, and a solder-nickel-based superalloy reaction layer. The solder-boron nitride reaction layer is formed by reacting nickel-containing solder with boron nitride, and contains TiN and TiB2.

2. The connecting joint according to claim 1, characterized in that, The solder-boron nitride reaction layer includes a boron nitride-Ti layer reaction layer, a Ti layer, and a solder-Ti layer reaction layer.

3. The connecting joint according to claim 1 or 2, characterized in that, The boron nitride ceramic is a hexagonal boron nitride ceramic; And / or, the boron nitride ceramic is in the form of sheets or blocks.

4. The connecting joint according to claim 2, characterized in that, The boron nitride-Ti layer reaction layer contains TiN; And / or, the thickness of the boron nitride-Ti layer reaction layer is 0.1-0.5 μm.

5. The connecting joint according to claim 2, characterized in that, The thickness of the titanium layer is 1-4 μm; And / or, the thickness of the solder-Ti layer reaction layer is 0.1-0.5 μm.

6. The connecting joint according to claim 1 or 2, characterized in that, The raw materials of the solder reaction layer include nickel-based amorphous powder and titanium hydride powder, with a mass ratio of 9:1 to 7:

3. And / or, the thickness of the solder reaction layer is 20-200 μm.

7. The connecting joint according to claim 1 or 2, characterized in that, The brazing filler metal-nickel-based superalloy reaction layer is a metal cladding layer; And / or, the thickness of the metal cladding layer is 5-25 μm.

8. The connecting joint according to claim 1 or 2, characterized in that, The shear strength of the connection joint is 0.4-4 MPa.

9. A method for preparing the connecting joint between boron nitride ceramic and nickel-based superalloy as described in claim 1, characterized in that, The method includes: (1) Preparation of nickel-based composite solder; (2) Place the nickel-based composite brazing filler metal between the boron nitride ceramic and the nickel-based high-temperature alloy surfaces to be welded, and press it with a mold; (3) Heat treatment to obtain the connecting joint.

10. The method according to claim 9, characterized in that, Before step (2), a titanium film is deposited on the surface of the boron nitride ceramic to be welded.